Konsep Pendidikan Islam Dalam Penguatan Moderasi Beragama - Arikarani, Yesi; Azman, Zainal; Aisyah, Siti; Ansyah, Fadillah Putri; Zakia Kirti, Tri Dinigrat (Edification Journal : Pendidikan Agama Islam, 2024)
In social life, there are certainly many differences that make us have to understand and respect the differences that exist, as is the case in Indonesia, which has a variety of ethnicities, religions, and cultures, so everyone must have an attitude of tolerance towards these things. In the concept of Islamic education, religious moderation must be strengthened because Islam teaches balance and a middle way in all areas of life. This journal was written to increase readers' insight into the importance of moderation. The author hopes that readers can apply the concept of Islamic education to strengthening religious moderation. The author used qualitative research in writing this journal. Qualitative research is descriptive research and tends to use analysis in library research. The data collection process uses references from various journals, articles, and relevant books. Therefore, by strengthening religious moderation, Islamic education can guide people to understand and practice Islamic teachings proportionally without falling into fanaticism, which can trigger conflict and division. There are several concepts of Islamic education that describe an attitude of religious moderation: 1) Tawassuth (choosing the middle way); 2) Tawazun (balance); 3) I’tidal (straight and firm); 4) Tasamuh (tolerance); 5) Musawah (equality); and 6) Shura (consideration). Islamic education can also teach openness and religious diversity so that people understand differences in religion and belief. Therefore, the concept of Islamic education plays a very important role in strengthening religious moderation as a benchmark for Muslims to live a diverse social life in order to create a peaceful social environment.